2010
DOI: 10.1155/2010/560349
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Projection Matrix for Compressive Sensing

Abstract: Compressive sensing (CS) is mainly concerned with low-coherence pairs, since the number of samples needed to recover the signal is proportional to the mutual coherence between projection matrix and sparsifying matrix. Until now, papers on CS always assume the projection matrix to be a random matrix. In this paper, aiming at minimizing the mutual coherence, a method is proposed to optimize the projection matrix. This method is based on equiangular tight frame (ETF) design because an ETF has minimum coherence. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 18 publications
2
92
0
Order By: Relevance
“…From the results, it showed that the optimized sensing matrix based on equiangular tight frame [6]can be improved the performance of face verification system using compressive sensing. Future improvements can be done by considering the noise in verifying a face so that the system can be implemented in practice also communication between client and server can be developed further so that it can communicate via the internet.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the results, it showed that the optimized sensing matrix based on equiangular tight frame [6]can be improved the performance of face verification system using compressive sensing. Future improvements can be done by considering the noise in verifying a face so that the system can be implemented in practice also communication between client and server can be developed further so that it can communicate via the internet.…”
Section: Resultsmentioning
confidence: 99%
“…However, the sensing matrix can further be optimized by minimizing the averaged mutual coherence of the equivalent dictionary. In this paper,sensing matrix optimization algorithms based on equiangular tight frame [6] is used. Fig.…”
Section: Compressive Sensing Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The method iteratively reduces large elements in the Gram matrix A T A directly, and then computes a new projection satisfying rank conditions associated with the desired number of measurements. Duarte-Carvajalino and Sapiro [7] addressed the same objective shortly thereafter as an eigenstructure problem, and achieved faster computations; Xu et al [8] followed with an approach based on the equiangular tight frame, and reported further improvements, although computing times are not given. These methods put no constraints on P and the outcome of optimization is dense in the general case, because implicit is the assumption that all of y is available.…”
Section: Problem Scenariomentioning
confidence: 99%